Appendicolith classification: physical and chemical properties of appendicoliths in patients with CT diagnosed acute appendicitis - a prospective cohort study - Vanhatalo, Sanja; Mäkilä, Ermei; Hakanen, Antti J.; Munukka, Eveliina; Salonen, Jarno; Saarinen, Timo; Grönroos, Juha; Sippola, Suvi; Salminen, Paulina (BMJ Group, 2026)
Objective Appendicoliths are associated with a more complicated course of acute appendicitis and failure of non-operative treatment. We aimed to update the appendicolith classification originally described in 1966 and to assess the association of appendicolith characteristics with appendicitis severity.
Design This prospective predefined MAPPAC-trial (ClinicalTrials.gov NCT03257423) substudy included patients with CT diagnosed appendicitis presenting with an appendicolith. CT visible appendicoliths were harvested at surgery, measured and characterised by morphological examination complemented with micro-CT and micro-X-ray fluorescence spectroscopy. Patients were categorised into two groups: appendicolith appendicitis without other complications and appendicolith appendicitis with complications (appendiceal gangrene, perforation and/or abscess). The association of appendicolith classification and characteristics with appendicitis severity was evaluated.
Results Of 78 patients with a CT appendicolith, 41 appendicoliths were collected and classified based on the degree of hardness into three classes. The hardest appendicoliths (class 3) were less common (19.5%) presenting with a stone-hard outer layer and concentrically layered inner structure around a core. The layered inner structure was also observed in class 2 appendicoliths, but was absent in soft, class 1 appendicoliths. Appendicolith hardness or measures (maximum length, diameter and weight) were not associated with appendicitis severity. The spatial distribution of the main inorganic elements of calcium and phosphorus varied within most appendicoliths.
Conclusion This updated classification confirms categorisation of CT visible appendicoliths into three classes based on their physical and chemical characteristics. The data on clinical and aetiopathological characteristics of appendicoliths is scarce and using this systematic classification would add to this understanding.